Effects of molasses supplementation on animal performance and carcass parameters of beef cattle: a meta-analysis - de Nazaré Santos Torres, Rodrigo [UNESP] (2023)
Molasses must be one of the most used foods in the diet of ruminant animals; however, there is no consensus on the effect of including molasses on carcass parameters. In this context, the objective was to evaluate the effect of including molasses in the diet of feedlot cattle on performance and carcass parameters. Thirteen peer-reviewed publications with 45 treatment means were included in the dataset. The effect of molasses in beef cattle diets was evaluated by examining the weighted mean differences (WMD) between molasses treatment (diet with molasses) and control diet (diet without molasses). Heterogeneity was explored by meta-regression and subgroup analysis using genetic type and experimental period, molasses in diet (g/kg dry matter (DM)), molasses type, concentrate in diet (g/kg DM), and forage type. The inclusion of molasses in the diet increased dry matter digestibility, but reduced NDF digestibility, carcass weight, subcutaneous, and visceral fat. The main sources of variation for the responses with molasses inclusion on intake, digestibility, performance, and carcass parameters were the level of molasses inclusion and the experimental period. In general context, the inclusion of molasses in the diet between 100 to 150 g/kg of DM did not affect performance and carcass parameters. However, the inclusion of molasses above 200 g/kg reduces the average daily gain and carcass weight.